2015
DOI: 10.1002/ccr3.284
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide for tocilizumab‐resistant ascites with TAFRO syndrome

Abstract: Key Clinical MessageTAFRO syndrome have been proposed as a rare variant of Castleman's disease. This article reports a case of a 56-year-old man with TAFRO syndrome who was successfully treated with thalidomide in spite of the refractoriness to prednisolone and tocilizumab. Thalidomide may be one of the treatment options for TAFRO syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…1 month after the administration of cyclosporin A (4 mg/kg /day) on day 51, the platelet count had increased to the normal range and the patient's ascites and pleural effusion had completely resolved. Furthermore, Tatekawa et al reported a 56-yearold man who had TAFRO syndrome [18]. Combined administration of tocilizumab and prednisolone improved lymphadenopathy, pleural effusion, anemia, thrombocytopenia, and hypoalbuminemia, but elevation of C-reactive protein Fig.…”
Section: Discussionmentioning
confidence: 97%
“…1 month after the administration of cyclosporin A (4 mg/kg /day) on day 51, the platelet count had increased to the normal range and the patient's ascites and pleural effusion had completely resolved. Furthermore, Tatekawa et al reported a 56-yearold man who had TAFRO syndrome [18]. Combined administration of tocilizumab and prednisolone improved lymphadenopathy, pleural effusion, anemia, thrombocytopenia, and hypoalbuminemia, but elevation of C-reactive protein Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Both iMCD‐TAFRO patients were anti‐IL‐6 nonresponders and all three iMCD‐NOS patients treated with anti‐IL‐6‐therapy responded. Importantly, there have been reports of iMCD‐TAFRO cases that have responded to anti‐IL‐6‐therapy and others that have not . The proteomic differences between the two groups may represent differences between clinical subtypes or be a signature of anti‐IL‐6 response.…”
Section: Discussionmentioning
confidence: 99%
“…A 12-year-old Japanese male was referred to us with pitting edema of lower limbs and high fever refractory to antibiotics for Some TAFRO syndrome cases refractory to tocilizumab have been reported, [6][7][8][9] but the timing of evaluating the efficacy of tocilizumab was too early. In randomized double-blind placebo-controlled trials of siltuximab for iMCD, a median time of 33 days was required to show a response to siltuximab in responders.…”
Section: A Pediatric Case Of Tocilizumab-resistant Tafro Syndrome Trementioning
confidence: 99%